Comparative proteomics analysis of Schistosoma japonicum developed in different Oncomelania snails as intermediate hosts - Liu, Gongzhen; Miao, Feng; Wang, Yongbin; Kou, Jingxuan; Yang, Kun; Li, Wei; Xiong, Chunrong; Zhang, Fengjian; Wang, Xinyao; Yan, Haoyun; Wei, Changyin; Zhao, Changlei; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Schistosomiasis is a tropical parasitic disease that seriously endangers humans and animals. In this study, two Oncomelania snails, Oncomelania hupensis (O. hupensis) and Oncomelania weishan (O. weishan), were infected with Schistosoma japonicum (S. japonicum) cercariae during the early period, and ICR mice were subsequently infected with two kinds of miracidia that developed in male and female adult worms. In this study, isobaric tags for relative and absolute quantification (iTRAQ) were used to identify four channels: 113, 115, 117, and 119. A total of 2364 adult schistosome proteins were identified, and 1901 proteins were quantitative. Our results revealed 68 differentially expressed proteins (DEPs) in female adult worms, including 24 upregulated proteins and 44 downregulated proteins, and 55 DEPs in male adult worms, including 25 upregulated proteins and 30 downregulated proteins. LC-MS/MS and bioinformatics analysis indicated that these DEPs are mainly concentrated in cellular composition, molecular function, biological function and catabolism pathways. In summary, this proteomics analysis of adult schistosomes that hatched in two intermediate hosts helps to improve our understanding of the growth and developmental mechanisms of S. japonicum.